2015
DOI: 10.1073/pnas.1508651112
|View full text |Cite|
|
Sign up to set email alerts
|

Direct evidence that suspensor cells have embryogenic potential that is suppressed by the embryo proper during normal embryogenesis

Abstract: The suspensor is a temporary supporting structure of proembryos. It has been proposed that suspensor cells also possess embryogenic potential, which is suppressed by the embryo as an effect of the embryo–suspensor interaction. However, data to support this hypothesis are not yet available. In this report, using an in vivo living cell laser ablation technique, we show that Arabidopsis suspensor cells can develop into embryos after removing the embryo proper. The embryo proper plays a critical role in maintainin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
59
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(60 citation statements)
references
References 43 publications
(41 reference statements)
1
59
0
Order By: Relevance
“…It has been suggested that the embryogenic potential of the suspensor cells is suppressed by the embryo proper and that the plant hormone auxin plays an important role in this process. Indeed, redistribution of auxin in the suspensor cells of Arabidopsis after laser ablation of the embryo proper precedes re-initiation of cell proliferation (Liu et al, 2015;Gooh et al, 2015).…”
Section: Disruption Of the Embryo Proper In The Cohesin-loading Complmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been suggested that the embryogenic potential of the suspensor cells is suppressed by the embryo proper and that the plant hormone auxin plays an important role in this process. Indeed, redistribution of auxin in the suspensor cells of Arabidopsis after laser ablation of the embryo proper precedes re-initiation of cell proliferation (Liu et al, 2015;Gooh et al, 2015).…”
Section: Disruption Of the Embryo Proper In The Cohesin-loading Complmentioning
confidence: 99%
“…The mechanism underlying this shift of cell fate is still unknown. Laser ablation experiments have shown that removal of the embryo proper results in the induction of an embryo-proper-like pathway in the terminally differentiated suspensor cells, suggesting that the embryo proper produces a signal suppressing the embryogenic potential of suspensor cells (Liu et al, 2015;Gooh et al, 2015). This developmental transition is associated with the redistribution of auxin.…”
Section: Atscc4 Is a Nuclear Protein Required For Embryonic Cell Fatementioning
confidence: 99%
“…From the phenotype of these mutants, a model was proposed that embryo-proper-like pathways in the suspensor are suppressed by the embryo proper during the process of normal embryo development (Schwartz et al, 1994). More recently, a combination of in vivo living laser cell ablation and microculture techniques allowed to demonstrate that the basal cell lineage has the potential to produce secondary embryos after the embryo proper has been removed (Gooh et al, 2015;Liu et al, 2015), indicating that the embryonic potential of the basal cell lineage has to be suppressed. Interaction between apical cell and basal cell lineage thus plays a critical role in basal cell fate determination, suggesting that there is cell-tocell communication between apical and basal cell lineage during the process of early embryogenesis.…”
Section: Cell Fate Determination Of Apical and Basal Cell Lineagesmentioning
confidence: 99%
“…18 Suspensor cells also have embryogenic potential, which is suppressed by the embryo proper during normal embryogenesis. 19 Following embryo removal, auxin gradually accumulates in the top suspensor cell, where cell division occurs to produce a new embryo. 19 Therefore, auxin redistribution appears to reprogram the fate of the suspensor cell and triggers embryogenesis in suspensor cells.…”
mentioning
confidence: 99%